Antioxidant activity of vitamin C and E versus oxidative stress induced by heavy metals in common carp (Cyprinus carpio) - Sahiti, Hazbije; Bislimi, Kemajl; Rexhepi, Agim; Kovaçi, Zehra; Dalo, Enis (Penerbit Universiti Kebangsaan Malaysia, 2023)
The present study was undertaken to investigate the antioxidant activity of vitamins C and E singly and together in modulating levels of Malondialdehyde (MDA), total protein, and glucose in different organs (gills, liver, & muscles) and plasma of common carp exposed to heavy metals (Pb, Cd, & Hg). The division of fish into two groups (control group and experimental group) was done after acclimatization. Seven days after exposure to heavy metals, the results showed a significant increase in the level of MDA in all organs of the experimental group (B) compared to those of the control group (A). Metal exposure caused a significant increase in the level of glucose in the liver and plasma (group B), while in muscles and gills, it caused a decrease in the amount of glucose (group B). Heavy metals have caused a slight decrease in total protein (gills, liver, & muscles). Seven days after exposure, the fish were split into three groups: one group was fed with vitamin C, another group with vitamin E, and the third group was fed with both vitamins (C & E). Results show that the addition of vitamins C and E as a food supplement resulted in the restitution of MDA and glucose values similar to those of the control group in all three investigated organs. But in terms of the amount of total protein, the results show that the addition of vitamins (C, E, & C+E) could not restore these values. Otherwise, in most cases, these two vitamins (C & E) administered together have shown more ameliorative effects than in the case of separate administration.